THE ROLE OF THE MRI EXAMINATION IN THE DIAGNOSIS AND MONITORING OF TUMORAL LESIONS OF THE PAROTID GLANDS - Mihaela- Roxana Popescu; Bogdan Ionut Dobrovat; Emilia Adriana Marciuc; Ana Cristina Istrate; Oana Raluca Temneanu; Daniela Pomohaci; Letiția Doina Duceac; Danisia Haba (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study: MRI (magnetic resonance imaging) is a non-invasive technique that uses magnetic fields and radio frequency waves to create detailed images of tissues and organs inside the human body. It has become one of the best diagnostic methods in recent decades due to its non-invasive, non- irradiating nature and its ability to detect modifications appeared at the level part mol and structures nervous. Pathology tumor of the glands parotid has a polymorphic appearance, with clinical and imaging similarities between tumoral lesions. In this context, MRI examination with the administration of paramagnetic contrast substance and the use of specific sequences such as DWI and advanced technologies, such as Dynamic contrast-enhanced (DCE)-MRI, show promising results in their differentiation.